EURASIAN ASSOCIATION OF CARDIOLOGY (EAC) GUIDELINES FOR THE DIAGNOSIS AND TREATMENT OF CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION (2020) - I. E. Chazova; T. V. Martynyuk; Z. S. Valieva; V. A. Azizov; R. S. Akchurin; A. A. Ansheles; O. Ya. Vasiltseva; T. N. Veselova; A. S. Galyavich; S. V. Gorbachevsky; N. M. Danilov; A. G. Edemskiy; et al. (Евразийский Кардиологический Журнал)
Disclaimer The EAC Guidelines represent the views of the EAC, and were produced after careful consideration of the scientific and medical knowledge, and the evidence available at the time of their publication. The EAC is not responsible in the event of any contradiction, discrepancy, and/or ambiguity between the EAC Guidelines and any other official recommendations or guidelines issued by the relevant public health authorities, in particular in relation to good use of healthcare or therapeutic strategies. Health professionals are encouraged to take the EAC Guidelines fully into account when exercising their clinical judgment, as well as in the determination and the implementation of preventive, diagnostic, or therapeutic medical strategies; however, the EAC Guidelines do not override, in any way whatsoever, the individual responsibility of health professionals to make appropriate and accurate decisions in consideration of each patient’s health condition and in consultation with that patient and, where appropriate and/or necessary, the patient’s caregiver. Nor do the EAC Guidelines exempt health professionals from taking into full and careful consideration the relevant official updated recommendations or guidelines issued by the competent public health authorities, in order to manage each patient’s case in light of the scientifically accepted data pursuant to their respective ethical and professional obligations. It is also the health professional’s responsibility to verify the applicable rules and regulations relating to drugs and medical devices at the time of prescription.